The importance of developing new mannan tests in the diagnosis of invasive candidiasis in oncology patients - O. Yu. Kutsevalova; Yu. Yu. Kozel; N. E. Nifantiev; A. V. Antonets; V. B. Krylov (Южно-Российский онкологический журнал, 2021)
The regimens of anticancer therapy have been intensified and methods of high-dose chemotherapy (HDCT) have been introduced for recent years which made it possible to achieve significant progress in the results of tumor treatments. Intensification of chemotherapy regimens in cancer patients leads to the emergence of risk factors of invasive candidiasis (IC) development: agranulocytosis, disruption of the integrity of the mucous membranes, prolonged use of CVC, repeated antibiotic therapy, long-term parenteral nutrition. Thus, intensification of anticancer therapy may be accompanied by an increase in infection-mediated mortality.IC is the most common invasive mycosis in Russia. More than 11 thousand cases of IC occur in our country every year. The frequency IC in Russia is 8.29 per 100 thousand of the population, which corresponds to the results of the LIFE study in European countries where this indicator varies from 2.2 to 11 per 100 thousand of the population. There are no clinical signs or symptoms specific for IC. It develops in patients with concomitant diseases, which significantly complicates the diagnosis. In this regard, an urgent issue is to improve the diagnosis of candidal infectious complications in cancer patients in order to optimize treatment by studying serological markers that have the greatest value in the diagnosis of infectious complications in cancer patients.